Hodnocení informačních výstupů krajských úřadů o životním prostředí - Máchová, Renáta; Bubáková, Pavla (Univerzita Pardubice, 2011)
This article is focused on the evaluation of information outputs of the regional offices of the environment. Portals of regional offices are monitored and the results of monitoring are evaluated. Purpose of evaluation is to get the best possible output from the current portals from the environment. Outputs that would best display the information as possible from areas of the environment could serve to create an environmental portal. This portal in the Czech Republic does not exist. There are only portals, which are closely specialized to a specific area of the environment. The only provider of summary environmental information are portals of regional offices.
Keywords: environment; portal; regional office; fuller's method; 3-levels AHP; monitoring